Evaluasi Minat Generasi Z dalam Melestarikan Tenun Ulos Sebagai Warisan Budaya di Kecamatan Siantar Utara - Seri Herlina Gea; Siti Nurhaliza Lubis; Yusmalinda Yusmalinda (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to evaluate Generation Z's interest in preserving ulos weaving as a cultural heritage in North Siantar District, Pematangsiantar City. Ulos weaving is a Batak cultural heritage with historical, philosophical, and social value, contributing to the community's cultural identity. However, globalization and modernization have influenced the mindsets and lifestyles of the younger generation, leading to a decline in interest in continuing the ulos weaving tradition. Generation Z faces a dilemma between the desire to preserve traditional cultural values and the demands of economics, social status, and modern lifestyle orientations. This study used a qualitative approach with a descriptive evaluative method. Data were collected through questionnaires from 62 Generation Z respondents who work as ulos weavers in North Siantar District. Data analysis was conducted to evaluate Generation Z's level of interest in preserving ulos weaving and identify influencing factors, including aspects of family business inheritance, economic and social status factors, and cultural awareness and appreciation. The results of the study indicate that Generation Z's interest in preserving the cultural heritage of ulos weaving stems from inheriting a family business (45%), social status (30%), and a desire to preserve Batak culture (25%). These three aspects indicate that Generation Z faces a dilemma between traditional values and the demands of modernization and economic needs. Therefore, strategies for preserving ulos weaving need to be directed at strengthening cultural education, innovating ulos products relevant to the tastes of the younger generation, developing the creative economy, utilizing digital media as a promotional tool, and providing policy support from the government and educational institutions to ensure the sustainability of ulos preservation, both culturally and economically.